Convalescent plasma therapy in the management of COVID-19 patients and its effect on morbidity and mortality - Madhav Prabhu; Harpreet Kour; Shivani Charuhas Bhagwat; Akash Ramaswamy; Arathi Darshan; Jayaprakash Appajigol (Wolters Kluwer Medknow Publications, 2023)
BACKGROUND: Since the beginning of the COVID-19 pandemic, there have been preliminary studies worldwide, hoping to shed some light on the efficacy of convalescent plasma therapy (CPT) in the management and recovery of SARS-CoV-2-infected patients. There is a dearth of such studies, especially from one of the world's second-worst hit country-India. This study aims to determine the effects of CPT on the clinical and biochemical profile, and overall mortality of patients suffering from moderate-to-severe SARS-CoV-2 infection. MATERIALS AND METHODS: After random selection of inpatients with COVID-19 disease, patients were matched for various characteristics and allotted into cases and control groups. This was done keeping a 1:2 ratio for cases and controls. Cerebral palsy (CP) therapy was administered to only cases, and these groups were compared. P < 0.05 was considered statistically significant. RESULTS AND CONCLUSIONS: Totally, 141 patients - 47 cases and 94 controls - were compared for the efficacy of CPT on clinical and biochemical profiles along with mortality benefit. It was found that CP therapy provided no significant morbidity and mortality benefit.